Abnormalities in the Polysomnographic, Adenosine and Metabolic Response to Sleep Deprivation in an Animal Model of Hyperammonemia - Marini, Selena; Santangeli, Olena; Saarelainen, Pirjo; Middleton, Benita; Chowdhury, Namrata; Skene, Debra J.; Costa, Rodolfo; Porkka-Heiskanen, Tarja; Montagnese, Sara (Frontiers in Physiology, 2017)
Patients with liver cirrhosis can develop hyperammonemia and hepatic encephalopathy (HE), accompanied by pronounced daytime sleepiness. Previous studies with healthy volunteers show that experimental increase in blood ammonium levels increases sleepiness and slows the waking EEG. As ammonium increases adenosine levels in vitro, and adenosine is a known regulator of sleep/wake homeostasis, we hypothesized that the sleepiness-inducing effect of ammonium is mediated by adenosine. Eight adult male Wistar rats were fed with an ammonium-enriched diet for 4 weeks; eight rats on standard diet served as controls. Each animal was implanted with electroencephalography/electromyography (EEG/EMG) electrodes and a microdialysis probe. Sleep EEG recording and cerebral microdialysis were carried out at baseline and after 6 hours of sleep deprivation. Adenosine and metabolite levels were measured by HPLC and targeted LC/MS metabolomics, respectively. Baseline adenosine and metabolite levels (12 of 16 amino acids, taurine, t4-hydroxy-proline and acetylcarnitine) were lower in hyperammonemic animals, while putrescine was higher. After sleep deprivation, hyperammonemic animals exhibited a larger increase in adenosine levels, and a number of metabolites showed a different time-course in the two groups. In both groups the recovery period was characterized by a significant decrease in wakefulness/increase in NREM and REM sleep. However, while control animals exhibited a gradual compensatory effect, hyperammonemic animals showed a significantly shorter recovery phase. In conclusion, the adenosine/metabolite/EEG response to sleep deprivation was modulated by hyperammonemia, suggesting that ammonia affects homeostatic sleep regulation and its metabolic correlates.